2010
DOI: 10.1096/fj.09-148007
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilium‐dependent mechanosensing is mediated by adenylyl cyclase 6 and cyclic AMP in bone cells

Abstract: Primary cilia are chemosensing and mechanosensing organelles that regulate remarkably diverse processes in a variety of cells. We previously showed that primary cilia play a role in mediating mechanosensing in bone cells through an unknown mechanism that does not involve extracellular Ca(2+)-dependent intracellular Ca(2+) release, which has been implicated in all other cells that transduce mechanical signals via the cilium. Here, we identify a molecular mechanism linking primary cilia and bone cell mechanotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
150
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(164 citation statements)
references
References 62 publications
13
150
0
Order By: Relevance
“…Ultrastructural studies have confirmed that mature chondrocytes possess an immotile primary cilium that has a microtubule axoneme core made up of a ring of nine microtubule doublets, but devoid of the central pair of microtubules (thus designated as 9+0) that motile cilia always have (called a 9+2 axoneme) [26]. Primary cilia have been well documented to serve as a nexus that integrates chemical and mechanical signals; in particular, they are considered as mechanosensors of fluid flow in many cell types including kidney epithelial cells, cholangioctyes or endothelial cells [54]. Primary cilia are also present on human mesenchymal stem cells, on arthritic chondroprogenitor cells (CPCs) [26] and on chondrocytes where they are unique sensory organelles that project into the pericellular matrix and interact with their close environment (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural studies have confirmed that mature chondrocytes possess an immotile primary cilium that has a microtubule axoneme core made up of a ring of nine microtubule doublets, but devoid of the central pair of microtubules (thus designated as 9+0) that motile cilia always have (called a 9+2 axoneme) [26]. Primary cilia have been well documented to serve as a nexus that integrates chemical and mechanical signals; in particular, they are considered as mechanosensors of fluid flow in many cell types including kidney epithelial cells, cholangioctyes or endothelial cells [54]. Primary cilia are also present on human mesenchymal stem cells, on arthritic chondroprogenitor cells (CPCs) [26] and on chondrocytes where they are unique sensory organelles that project into the pericellular matrix and interact with their close environment (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cilia have been shown to mediate mechanosensing in osteocyte-like cells. In response to dynamic flow, intracellular levels of cyclic adenosine monophosphate (cAMP) decrease rapidly in MLO-Y4 cells (Malone et al 2007;Kwon et al 2010;Fig. 2).…”
Section: Ift88mentioning
confidence: 99%
“…Integrins are transmembrane proteins that form attachments between the osteocyte cell process and the canalicular wall. Integrins connect the cytoskeleton to the extracellular matrix and function as mechanosensors (Kwon et al 2010;Nguyen and Jacobs 2013;Vaughan et al 2015). maturation, hypertrophy, terminal differentiation, and apoptosis (Kronenberg 2003;Zuscik et al 2008).…”
Section: Role Of Primary Cilia/ift In Cartilagementioning
confidence: 99%
“…It has recently been demonstrated that the primary cilium is involved in signal transduction in response to hydrostatic compressive loading of growth plate chondrocytes (Shao et al, 2011). Given that the primary cilium is known to act as a mechanosensory organelle in numerous orthopaedic cells (Malone et al, 2007;Kwon et al, 2010;Hoey et al, 2011;Shao et al, 2011;Hoey et al, 2012), it is possible that HP exerts its effects on joint tissue derived stem cells through any one of numerous signalling pathways (e.g. Hedgehog, Wnt) that acts through the primary cilia.…”
Section: T Vinardell Et Al Hydrostatic Pressure Maintains a Chondrogmentioning
confidence: 99%